# If (x + iy)3 = u + iv, then show that: It is given in the question that,

(x + iy)3 = u + iv

we know that, (x + y)3 = x3 + y3 + 3xy(x + y)

x3 + i3y3 + 3 × x × iy (x + iy) = u + iv

x3 + i3y3 + 3x2yi + 3xi2y2= u + iv

Now we know that, i3 = - i and i2 = -1

x3 – iy3 + 3x2yi – 3xy2 = u + iv

(x3 – 3xy2) + i(-y3 + 3x2y)= u + iv

Now, equating the imaginary and real part we will get,

u = (x3 – 3xy2), v = (-y3 + 3x2y)

According to question,  = x2 – 3y2 + 3x2 – y2

= 4x2 – 4y2

= 4(x2 – y2)

Thus, Hence, proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Polar & Euler Form of Complex Numbers on Argand Plane32 mins  Interactive Quiz Time - Polar & Euler Form of complex number58 mins  Practice session | Argument of complex numbers61 mins  Questions on Modulus & Conjugate of Complex Number62 mins  Modulus & Conjugate of Complex Number | Ready for a Quiz?48 mins  Questions Based on Polar & Euler Form of Complex Number63 mins  Interactive Quiz on Quadratic Equations-0252 mins  Special Quiz on Argument of complex numbers56 mins  Polar & Euler Form of Complex Number on Argand Plane58 mins  Interactive Quiz on Quadratic Equations73 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If |z + 1| = z + 2(1 + i), find z.

RD Sharma - Mathematics

Express each of the following in the form (a + ib) and find its conjugate.

(ii) (2 + 3i)2

(iii) (iv) (v) (vi) RS Aggarwal - Mathematics